The Portosystemic Shunt for the Control of Variceal Bleeding in Cirrhotic Patients: Past and Present - Petre Radu; Virgiliu-Mihail Prunoiu; Victor Strâmbu; Dragos Garofil; Roxana Elena Doncu; Eugen Brătucu; Laurentiu Simion; Maria-Manuela Răvaş; Mircea Nicolae Brătucu (Canadian Journal of Gastroenterology and Hepatology)
Based on an experience of more than 50 years in the treatment of portal hypertension (PHT), the authors review and analyze the evolution of the surgical portocaval shunt (PCS). We would like to provide an insight into the past of PCS, in order to compare it with the current state of the treatment of PHT complications. As a landmark of the past, we shall present statistics of more than 500 cases of PHT operated between 1968 and 1983. From this group, 238 patients underwent surgical portocaval shunting during a fifteen-year period. The behavior of the portal hemodynamics following PCS was studied and the postoperative decrease in portal pressure (PP), as well as the residual PP, were recorded. The portal manometric determinations were made by electronic recordings using the Hellige device and direct intraoperative recordings through the catheterization of a ramus in the portal area. The results of PCS are superposable, in terms of hemodynamic efficiency, with those of the intrahepatic shunt (TIPS—transjugular intrahepatic portosystemic shunt). The authors discuss the current place of PCS, in obvious decline in comparison with the situation 50 years ago. The current methods of controlling variceal bleeding represent obvious progress. PCS remains with very limited indications, in specific situations when the other therapeutic methods have failed or are not recommended.